2020
DOI: 10.3389/fcvm.2020.585165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhythm and Rate-Controlling Drugs in Patients With Permanent His-Bundle Pacing

Abstract: Introduction: Antiarrhythmic drug therapy can affect pacemaker parameters in both the atrial and ventricular myocardium. It is not known whether antiarrhythmic drugs impact His bundle pacing/sensing parameters and His to ventricle (H-V) intervals following permanent His bundle pacing (HBP). The aims of the study were to prospectively determine the influence of rhythm and rate-controlling drugs on pacing parameters and H-V conduction after His bundle lead implantation and to assess the impact of rhythm and rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It should be admitted that the proposed method has some limita- the visualization of HBS in inter-beat contour as shown in this work could still be acceptable for needy cases where continuous tracking of HBS is expected to be informative like for example, in studying the influence of pharmacological interventions (Su et al, 2020) and follow-up measurements where a conventional EPS recording involving fluoroscopic radiation may not be advisable (Muresan et al, 2019). There are ample scopes for refinements on the proposed method with respect to the automation of the IDWT process for fixing thresholds settings and adapting the methodology to encounter arrhythmic beats etc.…”
Section: Discussionmentioning
confidence: 98%
“…It should be admitted that the proposed method has some limita- the visualization of HBS in inter-beat contour as shown in this work could still be acceptable for needy cases where continuous tracking of HBS is expected to be informative like for example, in studying the influence of pharmacological interventions (Su et al, 2020) and follow-up measurements where a conventional EPS recording involving fluoroscopic radiation may not be advisable (Muresan et al, 2019). There are ample scopes for refinements on the proposed method with respect to the automation of the IDWT process for fixing thresholds settings and adapting the methodology to encounter arrhythmic beats etc.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, while the pacemaker itself may function normally, the capture threshold might elevate, possibly leading to ineffective capture of the myocardium and the induction of depolarization [ 36 , 53 ]. Notably, the effect of AADs on the capture threshold remained controversial due to contradicting reports [ 7 , [54] , [55] , [56] , [57] ]. This study also identified no significant association between AADs and capture threshold, which might be because LBBaP beyond the site of the block and AADs had no impact on the conduction beneath the his-bundle lead.…”
Section: Discussionmentioning
confidence: 99%
“…Flecainide increases the sinus node recovery time and delays intra-atrial and atrioventricular conduction, thus increasing the PR, QRS, and QT intervals without an increase in QTc duration [15]. It may cause an increase in the pacing threshold; however, no adverse impact has been noted in patients with pacemakers including those utilizing conduction system pacing [16, 17].…”
Section: Class Imentioning
confidence: 99%